Penjaminan Aset Daerah Oleh Pejabat - Mual, Dedi; Tjiptabudi, Jantje; Kuahaty, Sarah Selfina (CAPITAN: Constitutional Law & Administrative Law Review, 2025)
Management of regional assets is the responsibility of regional officials. Law Number 23 of 2014 mandates regional governments to manage assets based on the principle of regional autonomy. In the case of Bupati Kepulauan Meranti, Muhammad Adil, who is suspected of mortgaging regional assets in the form of the regent's office building to a bank, Article 4 of Ministerial Regulation Number 19 of 2016 states that "Regional Owned Goods may not be mortgaged or pledged to obtain loans, nor may they be transferred to another party as payment for invoices to the regional government, and cannot be seized, in accordance with applicable regulations." The research method used is a normative legal research type with a legal approach. Legal materials used include primary, secondary, and tertiary legal materials obtained through literature study. The legal materials collected are then processed and analyzed using qualitative techniques to answer research questions. Regional officials have authority based on Law Number 32 of 2004. They can secure assets such as land, buildings, and vehicles through attribution, delegation, and mandate approaches. However, it is important to note that regional officials mortgaging regional assets, as regulated in Article 4 of Ministerial Regulation Number 19 of 2016, must be avoided to prevent violations that can result in legal and financial consequences. The Legal Consequences of Regional Asset Guarantee Actions by Officials are categorized as acts against government law because guaranteeing assets by regional officials contradicts regulations as stipulated in Ministerial Regulation No. 19 of 2016, which can lead to legal and financial consequences.